Is depression screening in patients with acne critical?: reply from authors. (27th May 2018) - Vallerand, I.A.; Lewinson, R.T.; Parsons, L.M.; Lowerison, M.W.; Frolkis, A.D.; Kaplan, G.G.; Barnabe, C.; Bulloch, A.G.M.; Patten, S.B.
Abstract : Linked Articles: Unrue and Feldman. Br J Dermatol 2018;179 :226–227 .Vallerand et al. Br J Dermatol 2018;178 :e194–5 .